2017
DOI: 10.1111/tbed.12719
|View full text |Cite
|
Sign up to set email alerts
|

Rural veterinarian's perception and practices in terms of biosecurity across three European countries

Abstract: The implementation of biosecurity measures in the animal health and production context is quite broad and aims at limiting the risk of introduction and spread of diseases. Veterinarians play a major role in biosecurity as key informants on the subject for cattle holders, key players in terms of disease prevention/control and eradication programs, as well as key risk factor in terms of disease dissemination. Many biosecurity studies have highlighted professional visitors such as veterinary practitioners as repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
3
30
0
1
Order By: Relevance
“…A similarly lack of implementation of biosecurity measures has been observed on dairy farms elsewhere in Europe (7,11,20). The implementation of biosecurity plans on dairy farms is voluntary in almost all countries, with the exception of larger dairy farms in Denmark (21).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A similarly lack of implementation of biosecurity measures has been observed on dairy farms elsewhere in Europe (7,11,20). The implementation of biosecurity plans on dairy farms is voluntary in almost all countries, with the exception of larger dairy farms in Denmark (21).…”
Section: Discussionsupporting
confidence: 57%
“…The main limitations and strengths of the biosecurity measures applied in dairy cattle farms have been studied recently in several countries (710), as a preparatory step to develop greater awareness of the importance of each measure and the factors that might restrict its application. In Spain, despite the economic importance of milk production in some regions, current biosecurity practices on dairy farms have not been studied empirically although a recent study assessed perceptions and practices applied by rural veterinarians (11).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have identified several psychosocial factors in dairy farmers and veterinarians that might influence their decision on whether or not to implement biosecurity measures. Among these factors, it has been described that the attitude of farmers and veterinarians towards the implementation of biosecurity measures might be affected by the technical knowledge they have (Frössling & Nöremark, ; García & Coelho, ; Toma, Low, Vosough, Matthews, & Stott, ), the individual experiences they have lived (Broughan et al, ), the importance they can attribute to risks (Renault, Humblet, et al, ), and the benefits they can obtain from measures implemented (Ciaravino et al, ). Moreover, their behaviour towards the implementation of biosecurity measures has also been related to their perceived social pressure to apply these measures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…If farmers are well aware of the risk and usually prevent vehicle access to animal transit areas, they are unwilling or do not feel comfortable with imposing measures to visitors; they usually rely on their professionalism and tend to believe their boots and clothes are clean. Such belief is a real threat, as several studies demonstrated that most professional visitors do not implement suitably the BSM preventing the spread of infectious diseases (Nöremark & Sternberg‐Lewerin, ; Pritchard, Wapenaar, & Brennan, ; Renault et al., ; Sayers, Good, & Sayers, ; Shortall et al., ). Implementation rates were significantly higher in dairy farms for the use of farm‐dedicated clothes and boots.…”
Section: Discussionmentioning
confidence: 99%